Study of febrile thrombocytopenia in Malwa region of India - Yadav, Vishal; Singhai, Abhishek (Asian Journal of Medical Sciences, 2017)
Background: Febrile thrombocytopenia is the thrombocytopenia associated with fever. Diseases which commonly present with fever and thrombocytopenia are malaria, leptospirosis, septicemia, typhoid, arbovirus diseases such as dengue. Aims and Objectives: The study was intended to know the underlying etiology of febrile thrombocytopenia in Malwa region and its various presentations. Materials and Methods: This study was conducted at Department of General Medicine of a tertiary care centre for two years. Five-hundred adult patients (age >18 years) of febrile thrombocytopenia were evaluated for possible inclusion in this study. Routine investigations including complete blood counts, peripheral smear examination, kidney function tests, liver function tests, ultrasound of abdomen were done in all subjects. The specific investigations were done as and when indicated. Results: Out of 500 patients of febrile thrombocytopenia, 298 were male, while 202 were female. Commonest symptom after fever was malaise (83%) followed by nausea-vomiting (76%), headache (63.4%), jaundice (26.8%), easy fatigability (22.4%), bleeding manifestations (7.8%), cough (6.8%), dyspnea (5.8%), rash (2.4%) and delirium (1.4%). Dengue was found in 178 patients. Malaria was found in 122 patients. Other causes of febrile thrombocytopenia were septicemia (22 cases), leptospirosis (12 cases), chikungunya fever (10 cases), viral hepatitis (9 cases), enteric fever (9 cases), acute lymphoblastic leukemia (2 cases), non-hodgkin lymphoma (one case), disseminated tuberculosis (one case). Conclusion: Febrile thrombocytopenia is an important clinical condition commonly caused by infections, particularly viruses and malaria. Such studies will help in finding changing trends of locally prevalent infectious diseases and finding some new emerging diseases not prevalent in the particular region. Asian Journal of Medical Sciences Vol.8(5) 2017 83-86